Unscarred uterine rupture: a retrospective analysis in tertiary center - Verma, Madhureema; Bairwa, Radheshyam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine rupture is a catastrophic obstetrical emergency associated with a significant fetomaternal morbidity and mortality. Many risk factors for uterine rupture, as well as a wide range of clinical presentations have been identified. The objectives of the present study were to analyze the frequency, predisposing factors, maternal and fetal outcomes of unscarred uterine rupture. Methods: A retrospective analysis of cases of unscarred uterine rupture was conducted at the Department of Obstetrics and Gynaecology Jhalawar medical college Jhalawar Rajasthan from January 2009 to December 2016. Results: Our analysis comprised of 11 cases with unscarred uterine rupture. Incidence of unscarred uterine rupture is 0.01% or 1/10,000 deliveries. Conclusions: In our study there was no history of uterine scarring so the main predisposing factor are maltiparity and obstructed labour. The grand multiparas women and obstructed labour must be managed by proper trained personnel and in tertiary care center in order to avoid the morbidity and mortality.